2017
DOI: 10.1093/infdis/jix107
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Latent Mycobacterium tuberculosis Infection by Cellular Immune Profiling

Abstract: SummaryPersons with latent Mycobacterium tuberculosis infection (LTBI) vary by their risk of progression to tuberculosis but are clinically indistinguishable. We identified a cellular immune signature that correlates strongly with time since exposure, providing a rationale for immunological risk stratification to improve targeting of LTBI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
4
39
2
Order By: Relevance
“…Indeed, our estimated cell type and pathway analyses suggest that both cellular and molecular signatures of immune activation associated with recent exposure and could be interrogated by other modalities such as epigenetics. Immune cell differences between recently acquired and remotely acquired infection have been reported by others in single cohorts without longitudinal sampling (20,48). The high enrichment of B cell signaling in our signature is interesting, and a recent case control study in a single cohort showed that several IgG and IgA antibodies to M.tb antigens strongly discriminated (AUC > 0.90) active TB contacts who converted on TST from non-converters both at first known conversion and 3 months prior (49).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Indeed, our estimated cell type and pathway analyses suggest that both cellular and molecular signatures of immune activation associated with recent exposure and could be interrogated by other modalities such as epigenetics. Immune cell differences between recently acquired and remotely acquired infection have been reported by others in single cohorts without longitudinal sampling (20,48). The high enrichment of B cell signaling in our signature is interesting, and a recent case control study in a single cohort showed that several IgG and IgA antibodies to M.tb antigens strongly discriminated (AUC > 0.90) active TB contacts who converted on TST from non-converters both at first known conversion and 3 months prior (49).…”
Section: Discussionsupporting
confidence: 67%
“…Given that time since active TB exposure is the single strongest clinical risk factor for developing TB disease in immunocompetent persons, the finding that time since exposure and risk of TB, as predicted by the blood transcriptomic response, are independent in the GC6-74 study of healthy household contacts suggests that these signatures could be combined to possibly better predict risk of TB when the time of exposure is unknown (17,19,20). While the GC6-74 study was not powered for this particular secondary analysis, we assessed whether the highest 6gene score during longitudinal sampling allowed discrimination of subjects who did or did not progress to active TB disease during study follow-up.…”
Section: Application Of Reduced 6-gene Expression Signature Of Time Smentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report from the UK, the presence of TNF‐α‐only T effector cells was found to distinguish between individuals believed to have acquired TB either recently or remotely, as determined by epidemiologic and clinical data . While this study was relatively small, with only 59 total participants enrolled, and was conducted in a low‐burden setting, the prospect of a cellular immune signature capable of reliably identifying recent infection is exciting and warrants further study in other cohorts and high‐burden settings.…”
Section: Tools To Study Tb Transmissionmentioning
confidence: 89%
“…However, real-time, definitive diagnosis of recent exposure to Mtb at the individual level is not possible with any of the currently available tests (eg, TST, IGRA, chest X-ray, sputum analysis). Yet there are several recent reports of promising new approaches to identifying recent exposure, including a T-cell immune signature capable of differentiating recent from remote tuberculosis infection and a blood transcriptomic signature associated with greater risk of progression to active tuberculosis disease [ 41 , 42 ]. Although these signatures need to be validated in other settings, this type of biomarker of recent exposure would enable precisely targeted preventive therapy (akin to ring prophylaxis) and accelerate identification of tuberculosis “hotspots”—areas of high tuberculosis incidence—for earlier and more effective implementation of infection control measures [ 43 ].…”
Section: Current Transmission Research Needsmentioning
confidence: 99%